Gestational Age and Premature Rupture of Membranes with Neonatal Asphyxia - Destariyani, Elvi; Widiyanti, Desi; Yuniarti, Yuniarti; Yulyana, Nispi (Sarana Ilmu Indonesia (salnesia), 2024)
Neonatal deaths in Southeast Asia are caused by asphyxia and in Indonesia asphyxia is the cause of infant death. The research was conducted with the aim of analyzing the relationship between premature rupture of membranes (PROM) and gestational age with neonatal asphyxia. The research uses a quantitative approach with a case control type of research. The research was carried out at Argamakmur Hospital in December 2022. The research population was mothers who gave birth at Argamakmur Hospital in January - October 2022 with a sample size of 214 subjetc with details in the case group of 107 subject and the control group of 107 subject. Data collection uses a data collection format. The collected data was subjected to univariate and bivariate data analysis. Bivariate analysis uses the Chi-Square test. Based on data analysis, it is known that there is a relationship between premature rupture and neonatal asphyxia and there is a relationship between gestational age and neonatal asphyxia. It is hoped that health workers will provide communication, information and education on factors that cause asphyxia as an early detection effort and provide opportunities for health workers in the Arga Makmur Hospital environment to take part in skills training in managing asphyxia